Norwegian mathematics teachers’ and educational researchers’ perception of mpck items used in the teds-m study - Kaarstein, Hege (NOMAD Nordic Studies in Mathematics Education, 2014)
This paper presents how Norwegian teachers and educational researchers categorised a collection of items used in the international TEDS-M study. The teachers cate- gorised the items according to their own prototype understanding of mathematical content knowledge (MCK) and mathematics pedagogical content knowledge (MPCK), while the researchers categorised them after discussing how to understand MCK and MPCK and agreeing on what categorisation criteria to use. The results show that the item categorisation depended on the item characteristics. For example, multiple-choice items were associated with MCK and items asking the respondents to rewrite or reword a mathematical task were associated with MPCK. Furthermore, the results indicate a common Norwegian understanding of MPCK as the teachers’ and researchers’ categorisation largely coincided.